The Influence Of Kinesthetic Perception, Balance, Ankle Coordination And Motivation On Players' Drifting Skills Luwu Football School 2020 - Yaskar, Wahyudinata; Usman, Arifuddin; Suyudi, Imam (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
This research is about the influence of kinesthetic perception, balance, coordination, motivation and dribbling in Luwu Soccer School 2020 players. The population of all Luwu Soccer School 2020 players aged 15 years is 25 people. descriptive and path analysis SPSS 25. Research results: 1) There is no direct influence on kinesthetic perception on (0.008<0.05). 2) There is no direct effect of balance on motivation, (0.008<0.05). 3) There is no direct effect of balance on motivation (0.008<0.05). 4) There is direct influence of kinesthetic perception on herding (0.004>0.05). 5) There is a direct influence of balance on dribbling (0.000>0.05). 6) There is a direct influence of eye-foot coordination on dribbling with a coefficient value of (0.349< 0.486). 7) There is direct influence of kinesthetic perception through motivation on dribbling, (0.579>0.510). 8) There is a direct effect of balance through motivation on dribbling 0.953 0.034. 9.) There is a direct influence of eye-foot coordination through motivation on dribbling, 0.001 0.043. This shows that there is a direct influence between the kinesthetic perception variable through motivation on the ball dribbling ability of Luwu Soccer School players.